Designing Long-Lasting Products: Barriers for Design Consultancies. (May 2022) - Bendixen, A. F.; Jensen, C. N.; Schmidt, F.; Laursen, L. N.
Abstract: Past research shows there are significant barriers for creating long lasting products. In this paper we examine, the distinct collaborative barriers design consultancies face when striving to design long-lasting products for client firms. Data is collected through case studies (four months of observations and interviews) from three projects. Through the study we find indications, that the value chain intricacies, provide distinct interfirm barriers for creating long lasting products. These barriers include vision clashes, misalignment in the aspired manufacturing quality and price position.